Emerging attributes of adaptive governance in the global south - Akther, Shahana; Evans, James (Frontiers in Environmental Science, 2024)
Adaptive governance is widely considered an effective approach to address the complexities and uncertainties of socio-ecological systems. The application of adaptive governance to sustainable environmental governance in the global south has not been sufficiently explored. There is a gap in the literature in the global south, especially given its conceptual roots in the global north. A number of reviews identified some key conceptual and practical gaps related to adaptive governance principles and the challenges to implementing them. To address this gap, this paper presents a systematic literature review of adaptive governance scholarship focused on the global south published between 2003 and 2022. The review discusses adaptive governance's key principles and framings, as well as the challenges of implementing it in the global south. This paper examines the factors that influence the emergence of adaptive governance and how this framing has been used to understand effective environmental governance within the global south's diverse socio-political and institutional settings. The review specifically focuses on Africa and South Asia, which are densely populated with limited financial and institutional capacity. Sustainable environmental governance is crucial in these regions not only for the well-being of the population, but also for the health of the planet. A review of adaptive governance scholarship identified emerging attributes that improve government structures and processes, as well as proposed attributes that would minimize challenges and improve adaptive capacity. The key emerging attributes are formal and informal networks, social learning, community engagement and proposed attributes are flexible, integrated and participatory institutional governance, inclusive decision making, contextspecific strategies, accountability, and capacity development. These attributes provide a framework for adaptive governance scholarship for examining different governance structures and processes in different socioeconomic systems. This paper concludes with a framework for future research that can facilitate adaptive governance in the context of sustainable environmental management in the global south.